2017
DOI: 10.1186/s12960-017-0204-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of job satisfaction among nurses working in Ethiopian public hospitals, 2014: institution-based cross-sectional study

Abstract: BackgroundNurses play a pivotal role in determining the efficiency, effectiveness, and sustainability of health care systems. Nurses’ job satisfaction plays an important role in the delivery of quality health care. There is paucity of studies addressing job satisfaction among nurses in the public hospital setting in Ethiopia. Thus, this study aimed to assess job satisfaction and factors influencing it among nurses in Jimma zone public hospitals, southwestern Ethiopia.MethodsAn institution-based census was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
109
3
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(145 citation statements)
references
References 23 publications
13
109
3
13
Order By: Relevance
“…Notwithstanding its high perception, interactional justice was limited by reduced information sharing with, and lack of respect for subordinates, by supervisors among all professional sub-groups. Our findings support the evidence that health managers tend to be unsupportive, lack respect for junior staff and provide negative feedbacks during supervision [2,4,[18][19][20][21][23][24][25][26][27]. The study further revealed that nurses and AHPs had significantly lower perception of interactional justice than doctors, which contrasts insignificant differences in interactional justice between doctors and non-doctors found in a previous Nigerian study [11].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Notwithstanding its high perception, interactional justice was limited by reduced information sharing with, and lack of respect for subordinates, by supervisors among all professional sub-groups. Our findings support the evidence that health managers tend to be unsupportive, lack respect for junior staff and provide negative feedbacks during supervision [2,4,[18][19][20][21][23][24][25][26][27]. The study further revealed that nurses and AHPs had significantly lower perception of interactional justice than doctors, which contrasts insignificant differences in interactional justice between doctors and non-doctors found in a previous Nigerian study [11].…”
Section: Discussionsupporting
confidence: 87%
“…Doctors lacked respect for other health professional [16]. Health managers tend to be authoritarian, unsupportive, overuse behavioral control, lack respect for junior staff and provide negative feedbacks during supervision [2,4,[18][19][20][21][23][24][25][26][27].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…Nurses, as the largest and most important members of health care organizations, have an important role in promoting health community [14]. Nurses' job satisfaction is a phenomenon that is affected by many variables [15]. Several factors such as support of managers, communication with colleagues, the nature of the job, job security, and the amount of salary and benefits have impact on the job satisfaction of nurses [16].…”
Section: Introductionmentioning
confidence: 99%
“…Nurses, who provide direct health care are the largest health care cadre in the health care system [1][2][3]. But, the global shortage of nurse and its negative impact on health care is reaching a critical level and many nurses continue to voluntarily leave their workplaces and profession before the normal age of retirement [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Their job satisfaction and retention to remain employed determines the quality of the care they provided. Job satisfaction is referred as all the feelings that an individual has about his/her job or the positive feeling individuals have about their jobs, their career and for whom they work [2,[6][7][8][9][10]. Job satisfaction is not just the money or the fringe benefits, but the feelings employees receive from the work itself [11,12].…”
Section: Introductionmentioning
confidence: 99%